Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2481384
|View full text |Cite
|
Sign up to set email alerts
|

Making touchscreen keyboards adaptive to keys, hand postures, and individuals

Abstract: We propose a new approach for improving text entry accuracy on touchscreen keyboards by adapting the underlying spatial model to factors such as input hand postures, individuals, and target key positions. To combine these factors together, we introduce a hierarchical spatial backoff model (SBM) that consists of submodels with different levels of complexity. The most general model includes no adaptive factors, whereas the most specific model includes all three. Considering that in practice people may switch han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 24 publications
(38 reference statements)
1
36
1
Order By: Relevance
“…A comparison with adjusted p values (Holm-Bonferroni method) over all subjects and methods for different speeds and over all subjects and speeds for different input techniques was performed (due to the large number of tests and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 It is interesting to observe that for all measurement conditions the resulting adjusted pvalues suggest there is a different underlying process responsible for the generation of the observed densities. These results seem to suggest that for a particular walking speed, the gait phase data could be used as an additional feature (especially in on-the-go scenario) to infer which input technique is being used and possibly improve on detection rates reported in the literature (Goel, Wobbrock & Patel, 2012, Ouyang, Partridge & Zhai, 2013. The same analysis could be achieved for Figure 17b, i.e.…”
Section: (Figure 17 About Here)supporting
confidence: 65%
See 1 more Smart Citation
“…A comparison with adjusted p values (Holm-Bonferroni method) over all subjects and methods for different speeds and over all subjects and speeds for different input techniques was performed (due to the large number of tests and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 It is interesting to observe that for all measurement conditions the resulting adjusted pvalues suggest there is a different underlying process responsible for the generation of the observed densities. These results seem to suggest that for a particular walking speed, the gait phase data could be used as an additional feature (especially in on-the-go scenario) to infer which input technique is being used and possibly improve on detection rates reported in the literature (Goel, Wobbrock & Patel, 2012, Ouyang, Partridge & Zhai, 2013. The same analysis could be achieved for Figure 17b, i.e.…”
Section: (Figure 17 About Here)supporting
confidence: 65%
“…The authors also noted that the typing speed (expressed in words per minute) was not significantly affected with inclusion of a posture-adaptive keyboard. This approach was further refined in (Yin, Ouyang, Partridge & Zhai, 2013) to include a user-specific posture adaptive keyboard. In the paper, an elaborate hierarchical model was used which reduced the language-model independent error rate by 13.2% over the baseline model.…”
Section: Role Of Finger Posementioning
confidence: 99%
“…Later, Goel et al [7] examined the user's touch pattern to distinguish between the three input postures to improve text entry. Yin et al [27] also used hand posture to enhance text entry on touchscreen keyboards and reported that their method could differentiate single finger and two thumbs typing with an accuracy of 86.4%.…”
Section: One-and Two-handed Interactionsmentioning
confidence: 99%
“…Several papers have examined typing dynamics and gesturing on small physical keyboards and mobile (soft) keyboards (e.g. [3,9,13,25,35,43]). The papers considering modern typing have involved laboratory studies with small sample sizes.…”
Section: Introductionmentioning
confidence: 99%